Efectos de la aplicación de la abonadura orgánica en el rendimiento y producción de biomasa verde del cultivo de avena (avena sativa l.) - Reascos Estrada, Josè Miguel (2015)
The research was conducted in the village of San Pedro de Huaca of the province of Carchi, the same that is at a 77º west longitude of 43'36 "north latitude and 0º 20 '10" and altitude of 2923 meters. The area has annual average temperature of 12 °C and average annual rainfall of 1230 mm, relative humidity of 78% and 187.9 heliophany h / sol year. According to the classification of Holdridge the canton San Pedro de Huaca responds to ecological formation of humid forest Montano Alto (bh-MA). The aim of this study was to determine the production of green biomass through the cultivation of oats (Avena sativa L.) under three organic fertilizer and chemical fertilizer. As genetic material Avena Sativa variety used Forage Nacional, whose origin is from the Ecuadorian mountains. The treatments were constituted by three types of organic fertilizers based Bocashi, Ecoabonaza and Bovinaza (30000 Kg / ha), the combination of the Bocashi + Ecoabonaza, Ecoabonaza + Bovinaza and Bovinaza + Bocashi (1500 kg / fertilizers must c / u) a chemical N 30 - P 25 - K 30 and the control treatment without fertilization, so the block design was used completely at random (DBCA) with eight treatments and four repetitions, where all variables were subjected to analysis of variance using Duncan test 5%.......